Passenger Perspectives on the Vision of Sustainable Rail Transport Development - Motowidlak, Urszula; Chomicz, Gabriela; Jaksik, Daniel; Śmietana, Kacper (Towards Sustainable Transport in Logistics and International Trade, 2025)
The aim of this chapter is to present how rail transport users perceive sustainable development and how railway companies can use this feedback to improve, manage, and adapt their services. The research methodology is based on the analysis of survey results conducted among passengers, focusing on their perception of service quality, the environmental impact of railways, and the efficiency of infrastructure and resource management. The results point to the growing importance of ecological awareness among passengers, which influences their choice of transport mode. Although the study’s local scope may limit generalizability, the conclusions have strong applicative potential. Practical implications include the opportunity for rail operators to align their strategies with user expectations. The originality of the chapter lies in demonstrating the connection between passenger feedback and the strategic directions of railway development in the context of sustainability.